Brother against brother - Dixon, Franklin W. (New York : Pocket Books, 1988)
Carrying a message warning a federal witness about a hit man, Joe is ambushed, loses his memory and thinks Frank is the enemy.
'An Archway paperback.'
Koleksi sumbangan Prof. Dr. Ding Choo Ming.
Keywords: Mystery -- Fiction; Detective and mystery stories; Young adult fiction